Analisis Kebijakan Pengembangan Pendidikan (Studi Pembelajaran Daring (Online) di Masa Pandemi Covid-19 - Hairuddin Cikka; M. Iksan Kahar (Madika: Jurnal Politik dan Governance, 2021)
Covid-19 has had a tremendous impact, especially in the field of education, both higher education and basic education. One of the impacts of the covid-19 pandemic is the implementation of a learning system that is carried out online (on a network) from their respective homes which tends to use technology as a learning medium, sometimes there are obstacles in its application. In addition, several obstacles that arise in the implementation of online learning include the first, the difficulties of teachers in managing online learning and are still focused on completing the curriculum. Second, not all parents are able to optimally accompany their children to study at home because they have to work or have the ability to be a child's learning companion. Third, the students also have difficulty concentrating on studying from home as well as increasing saturation which has the potential to cause health problems. Distance learning during the Covid-19 pandemic is a challenge in education in Indonesia. Some of these challenges or obstacles are in the form of unequal mastery of science and technology among teachers or educators, problems with internet access which causes not all students to participate, and the high cost of learning quotas. Therefore, synergy, serious, systematic, and sustainable efforts are needed from all relevant parties including families, communities, and the government to resolve existing educational problems. All of these improvement efforts can of course only take place properly if there are government policies that are a shared view of life and policies that can provide solutions to existing problems related to the COVID-19 pandemic, in this case the government is of course the front line in making and determining policies. solution education.